Qualitative story completion: Possibilities and potential pitfalls. Issue 1 (2nd January 2019) - Braun, Virginia; Clarke, Victoria; Hayfield, Nikki; Frith, Hannah; Malson, Helen; Moller, Naomi; Shah-Beckley, Iduna
ABSTRACT: Virginia Braun, Victoria Clarke, Hannah Frith, Nikki Hayfield, Helen Malson, Naomi Moller, and Iduna Shah-Beckley came together at the University of the West of England (UWE) in July 2017 to discuss and share their enthusiasm for the story completion method. Virginia nominally "led" the discussion to keep us on track. This is a transcript of the discussion, edited by the Special Issue editors, principally Hannah Frith, which we have all read and commented on. The discussion begins with the contributors introducing themselves and their experience of the story completion method. It then identifies a series of "knotty issues" about story completion which we explored: 1) what can stories tell us?; 2) research practicalities, comparative design, and sample size; 3) what happens when story completion doesn't go to plan?; and 4) getting published. The conversation ends by considering "future possibilities for story completion research." Our aim was not to reach consensus of definitive "answers" but to debate and gain perspective on an open issue. Hence, we reach no "conclusion" for any of these issues.